Effects on Performance, Egg Quality Criteria and Cholesterol Level of Adding Different Ratios Flaxseed Oil Instead of Sunflower Oil to Compound Feed of Laying Hens - Tuğba Bingöl; Çağri Kale; Fatma Özkan; Suphi Deniz; Duran Bolat; Selçuk Altaçlı (Journal of Agricultural Sciences)
This study was conducted to examine the effect on performance, egg quality criteria and egg cholesterol level of adding different ratios of flaxseed oil instead of sunflower oil to the compound feed of laying hens. A total of 210, 30-week old Lohmann LSL laying hens were acquired for the study. The study groups consisted of a control group (5% sunflower oil (SO) + 0% flaxseed oil (FO) and trial 1 (4% SO + 1% FO), trial 2 (3% SO + 2% FO), trial 3 (2% SO + 3% FO), trial 4 (1% SO + 4% FO) and trial 5 (0% SO + 5% FO) groups. The study lasted for 8 weeks. The feed consumption was not different among the experimental groups. Feed utilization rate was higher in group 2 compared to those of other between 0-8 weeks (P<0.001). Between weeks 0 to 8, all trial groups were found have significantly higher levels of linoleic acid, one of the fatty acids found in yolk, compared to the control group (P<0.001). Additives were not found to affects levels of cholesterol in yolk, with no significant differences found between groups. In short, sunflower oil and flaxseed oil added to laying hen rations did not create any differences in terms of egg quality criteria or egg cholesterol levels, but higher levels of flaxseed oil added to the rations resulted in linearly higher levels of linolenic acid content of yolk, and use of the two oil additives together increased egg yields.